Ф.М.Достоевскийн зохиол дах философийн үзэл санааны үүсэл хөгжлийн тухай - Н., Хасбагана (Mongolian Studies, 2023)
Dostoevsky’s every character in the novel is absorbed with the philosophical ideas. In the midst of a difficult life, his philosophical ideas were gradually formed from the Christian religion concepts, such as atonement, purity and faith in the power of pure heart. He made efforts to create a Russian religious ideology.